Loading of Co3O4 onto Pt-modified nitrogen-doped TiO2 nanocomposites promotes photocatalytic hydrogen production. Issue 41 (12th May 2017) - Wei, Wen-Dong; Liu, Xiang-Yu; Cui, Shi-Cong; Liu, Jin-Gang
Abstract : Loading of Co3 O4 onto a very low content (0.02 wt%) Pt-modified N–TiO2 nanocomposite significantly promotes the efficiency of photocatalytic hydrogen production. Abstract : Photocatalytic water splitting has been considered as one of the most promising methods to produce hydrogen as a source of clean fuel. Use of co-catalysts and elemental doping in TiO2 has been extensively explored for effective photocatalysis. Here we report the synthesis of visible light responsive Pt and Co3 O4 co-modified nitrogen-doped TiO2 (N–TiO2 ) nanocomposites for efficient photocatalytic hydrogen production. Pt–Co3 O4 (S)/N–TiO2 (PCNT(S)) and Pt–Co3 O4 (D)/N–TiO2 (PCNT(D)) composites were synthesized by one- and two-step methods, respectively. Experimental results showed that additional loading of Co3 O4 onto a very low content (0.02 wt%) Pt-modified N–TiO2 nanocomposite significantly increases the efficiency of photocatalytic hydrogen production. Catalyst composites prepared by the two-step method, where close interaction occurred between the surface-loaded Co3 O4 and Pt on the N–TiO2 nanoparticles, showed much higher photocatalytic activity for hydrogen production than that prepared by the one-step method, where Co3 O4 is evenly dispersed in N–TiO2 . The position of the co-catalyst Co3 O4 in TiO2 has a significant effect on the photocatalytic properties of the prepared photocatalysts.